Acute effect of single-session physio-ball wall squat training on knee activereposition sense and isokinetic parameters in sedentary female collegiatestudents: an experimental study - Ameer, Mariam; Al Abbad, Ammar; Subbarayalu, Arun Vijay; Bahey El-Deen, Heba; Alserhani, Shahad; AL Arjan, Elaf; AL Ihawy, Wessam; AL Ruwaili, Njoud; Kamel, Mohamed (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. The current study aimed to examine the acute effect of physioball wall squat training on knee joint active repositionsenses and isokinetic parameters of knee flexion and extension in sedentary collegiate female students.Methods. An experimental study was conducted with sixty sedentary female college students aged between 18 to 25 whowere divided into two groups. The experimental group of 30 participants performed Swiss ball wall squats, spanning threesets of 12 repetitions each, with 30-second rest intervals between sets. The control group of 30 participants stood with a Swissball positioned behind their backs, replicating the same parameters as the experimental group but without squatting. The isokinetic4 Pro device measured active knee joint repositioning senses and isokinetic parameters of knee flexion and extension.Results. The findings revealed notable improvements in active knee repositioning senses and all isokinetic parameters ofknee flexion and extension (p < 0.05) in the experimental group post-training when compared to the control group. Therewere also significant differences detected between pre- and post-Swiss ball training intervention in the experimental groupfor all variables (p < 0.05).Conclusions. These results suggest that Swiss ball wall squat training could enhance knee joint position senses and isokineticparameters, potentially reducing knee injuries in sedentary individuals.
Keywords: exercise ball; kinesthesis; knee joint; muscle strength; females; sedentary behaviour